Hematological, serum biochemical results, and treatment approach of an Arabian mare with squamous cell carcinoma of the vulva - case report - Safak, T.; Yilmaz, O.; Risvanli, A.; Akdeniz-Incili, C. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2022)
A 20-year-old Arabian mare, was brought to the obstetrics and gynecology clinic with the complaint of an unknown wound in the genital area. Although the mare's general condition was good, examination of the genital area revealed a wide-open wound in the vulva and posterior vagina, characterized by fibrotic growth. The biopsy sample was sent to the pathology laboratory. A diagnosis of squamous cell carcinoma (SCC) was made after histopathological examination. Blood samples for serum biochemistry and hematological tests were collected from the jugular vein. Hematological and serum biochemical findings are generally used to diagnose diseases in animals and humans. Hematological and serum biochemical findings are important with genital SCC. Therefore, the findings of these values are given in this case report.
Resultados hematológicos, bioquímicos séricos e abordagem de tratamento de uma égua Árabe com carcinoma escamoso de células da vulva - relato de caso
Keywords: mare; serum hematological results; squamous cell carcinoma